Building and developing a team of Vietnamese youth according to Ho Chi Minh's will - Dr. Mai Quoc Dung, Mai Quoc Dung; Nhung, Hoang Thi; Trang, Hoang Thi (International Journal of Multidisciplinary: Applied Business and Education Research, 2022)
In Ho Chi Minh's thought, the issue of caring, fostering and educating the young generation holds an extremely important position. Because youth is the backbone of the nation, the future of the nation. In his Will, Ho Chi Minh once again admonished: "The Party needs to take care of educating them in revolutionary morality, training them to become heirs to build socialism that is both "pink" and at the same time "specializing", nurturing the revolutionary generation for the next generation is a very important and very necessary thing. Especially in the current period, with the process of deep international integration with the rapidly developing science and technology, Vietnamese youth need to cultivate their own revolutionary morality and adapt to the development of the world, having a breakthrough thinking, firmly overcoming all difficulties, always worthy of their position and role, with enthusiasm, energy, strong will to rise, living in a harmonious environment Peace, renewal and development of the country, Vietnamese youth will definitely uphold the pioneering spirit, bravery, solidarity and creativity, contributing to the construction and development of an increasingly prosperous and happy country.